MORPHOLOGICAL INTERFERENCE ON STUDENT’S WRITING - Muziatun Muziatun; Indri Wirahmi Bay; Sitti Maryam (Indonesian EFL Journal, 2020)
The aim of this research is to find out the types of morphological interference on students' English writing. Through qualitative research method applying a design of the case study, twenty of university students were chosen. Data were collected from written tests and classified based on the Politzer and Ramires (1973) on theory of Linguistic Category. The results revealed that, whilst it is inevitable that the English morphology features governed by the distinctive rules and systems have been the potential target for interference taking place, Bahasa Indonesia, which stands as the official language, becomes the source of transfer. From six types of morphological interference based on Polizter and Ramirez’ (1973), in this study the writer only found three of them. These types encompass of the morphological properties from the use of article, plural marker and simple past tense. Furthermore, there are 40 morphological mistakes in total, in which four mistakes represent the intralingual transfer and 36 data describe the interference. In terms of the mistakes made as a result mostly from the interference transfer. This study makes a significant contribution to the teaching and learning process of linguistic interference.Keywords: linguistic interference; morphology; students’ writing.